PENGEMBANGAN MEDIA PEMBELAJARAN POT SUSUN (STACKED POTS) UNTUK MENINGKATKAN KETERAMPILAN BERHITUNG SISWA - Ulfa, Nanik; Aliyah, Wakhidatul (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This research is motivated by the low numeracy skills of second-grade students at MI Al - Ishlah Kalipare. There are several factors contributing to these numeracy skills, including: 1) students' methods of addition and subtraction and determining the place value of hundreds, tens, and units. 2) Lack of mathematics learning media. To address these issues, the researcher developed a learning media called